Accelerated acidification by inoculation with a microbial consortia in a complex open environment. (September 2016) - Yu, Jiadong; Zhao, Ye; Liu, Bin; Zhao, Yubin; Wu, Jingwei; Yuan, Xufeng; Zhu, Wanbin; Cui, Zongjun
Highlights: Use bioaugmented acidification to produce methane in a complex environment. Bioaugmentation accelerated substrate degradation and organic acid yield in 3 days. High-throughput sequencing demonstrated that bioaugmentation is effective. Abstract: Bioaugmentation using microbial consortia is helpful in some anaerobic digestion (AD) systems, but accelerated acidification to produce methane has not been performed effectively with corn stalks and cow dung. In this study, the thermophilic microbial consortia MC1 was inoculated into a complex open environment (unsterilized and sterilized systems) to evaluate the feasibility of bioaugmentation to improve acidification efficiency. The results indicated that MC1 itself degraded lignocellulose efficiently, and accumulated more organic acids within 3 days. Similar trends were also observed in the unsterilized system, where the hemicellulose degradation rate and organic acid concentrations increased significantly by two-fold and 20.1% (P < 0.05), respectively, and clearly reduced the loss of product. Microbial composition did not change obviously after inoculating MC1, but the abundance of members of MC1, such as Bacillus and Clostridium, increased clearly on day 3. Finally, the acidogenic fluid improved methane yield significantly (P < 0.05) via bioaugmentation.